Kontribusi kompetensi guru terhadap kualitas layanan akademik di MAN se-Kabupaten Kulon Progo - Sukapsih, Esti; Supriyoko, Supriyoko (Indonesian Journal of Educational Management and Leadership, 2024)
Purpose − The aim of the study was to determine the contribution of educator competencies to academic service quality, to know the contribution of pedagogic competence to academic service quality, to know the personality competency contribution to service quality, to know the contribution of professional competence to academic service quality, and to contribute social competence to academic service quality in MAN Kulon Progo Regency. Method − This type of research is quantitative research. The variables of this study are pedagogical, personality, social, professional, and academic service quality competencies. The population in this study were 134 teachers. The sample of this study was 100 respondents, taken proportionally random sampling with an error rate of 5%. The data collection technique uses a questionnaire. The analysis uses multiple linear regression. Findings − Conclusion of the study: teacher competence contributes positively to academic service quality, meaning that the higher the competency of the teacher, the higher the quality of academic services. Pedagogic competence contributes positively to the quality of academic services, meaning that the higher the pedagogical competence, the higher the quality of academic services. Personality competencies contribute positively to academic service quality, meaning that the higher the personality competency, the higher the quality of academic services. Professional competence contributes positively to academic service quality, meaning that the higher the professional competence, the higher the quality of service for the academy. Social competence contributes positively to academic service quality, meaning that the higher the social competence, the higher the quality of academic services.